Pengaruh Harga, Brand Image, Dan Kepuasan Konsumen Terhadap Repurchase Pada Kentucky Fried Chicken (KFC) Kota Probolinggo - Dini Lestari; Muhammad Syarif Hidayatullah Elmas; Dedi Joko Hermawan (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
The object of this research is Kentucky Fried Chicken (KFC) in Probolinggo City. This study aims to determine the effect of price, brand image, and customer satisfaction on repurchase, either partially or simultaneously. The type of research used is a type of quantitative research with a causality approach (a causal relationship). The sampling technique uses Probability Sampling with the Simple Random Sampling method. The population of this study is consumers who buy directly at Kentucky Fried Chicken (KFC) Probolinggo City in May and June 2023, with a sample of 100 respondents.The research results show: There is an influence between price, brand image, and customer satisfaction partially on repurchase.